2022
DOI: 10.3390/nu14214566
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Novel Food Composed of Leucine, Omega-3 Fatty Acids and Probiotic Lactobacillus paracasei PS23 for the Treatment of Sarcopenia in Elderly Subjects: A 2-Month Randomized Double-Blind Placebo-Controlled Trial

Abstract: Sarcopenia is a complex process characterized by a progressive decrease in muscle mass and strength. Various nutrients have been shown to be effective in supporting muscular performance. This randomized clinical trial aimed to evaluate the effectiveness of a 2-month administration of food for special medical purposes composed of omega-3 fatty acids (500 mg), leucine (2.5 g), and probiotic Lactobacillus paracasei PS23 (LPPS23), on appendicular lean mass (ALM), muscle performance, inflammatory status, and amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 62 publications
1
14
0
4
Order By: Relevance
“…In the study of Rondanelli et al, probiotics, leucine, and omega-3 fatty acid were used as potential nutritional supplements in the treatment of sarcopenia, which were largely similar to the present study in terms of constituents. The results of the study, consistent with the findings of the present study, showed an increase in the muscle mass of the limbs, grip strength, and also a significant decrease in visceral fat 40 . In addition, in our study, the intervention groups of exercise and nutrition showed a small amount of weight gain or weight change compared to other groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the study of Rondanelli et al, probiotics, leucine, and omega-3 fatty acid were used as potential nutritional supplements in the treatment of sarcopenia, which were largely similar to the present study in terms of constituents. The results of the study, consistent with the findings of the present study, showed an increase in the muscle mass of the limbs, grip strength, and also a significant decrease in visceral fat 40 . In addition, in our study, the intervention groups of exercise and nutrition showed a small amount of weight gain or weight change compared to other groups.…”
Section: Discussionsupporting
confidence: 92%
“…Another supplement, Vit D3, has been used in different ranges, but the effect of this utilization is controversial and may depend on the level of physical activity of the consumer. These scenarios showed that probiotics' co-administration with protein-contained food (Amino acid-induced leucine) significantly increases maximum concentrations and levels of Amino acids, especially methionine, histidine, valine, leucine, isoleucine, tyrosine 39 , total BCAA 39 , 40 , and total essential amino acids, which is an important component of sarcopenia therapeutic intervention. On the other hand, prebiotics administration causes an increase in provitamin D3 41 , hence resolving vitamin D deficiency in sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, as discussed in Section 3.1 , Lactobacillus is considered as one of the most promising probiotics against sarcopenia with its supplementation being associated with improvements in muscle mass and physical function in both mouse models and human beings [ 68 , 159 , 160 ]. In particular, the administration of Lactobacillus paracasei , leucine and omega-3 fatty acids was particularly effective in improving muscle mass and function in a group of older frail individuals with an average age of 79.7 years old [ 161 ]. Observational studies suggest that the microbiota composition of subjects with sarcopenia and physical frailty may be characterized by increased representation of Lactobacillus spp.…”
Section: Interaction Between Phenolic Compounds and Microbiota: Possi...mentioning
confidence: 99%
“…Other studies provided LC n -3 PUFA as part of a multi-ingredient supplement, where it is not possible to delineate the action of LC n -3 PUFA, and have shown mixed results. For instance, improvements in appendicular lean mass, grip strength and physical function were observed following 2 months of supplementation with leucine, probiotics and LC n -3 PUFA in people with sarcopenia [26], although a lack of control group compromises the reliability of these findings. Furthermore, 6 months of combined LC n -3 PUFA (4 g/day), whey protein isolate (8 g/day), vitamin D3 (400 IU/day), and resveratrol (150 mg/day) supplementation resulted in improved grip strength and physical function in sedentary older adults [23].…”
Section: Randomised Controlled Trialsmentioning
confidence: 99%